Lak Chang: A reconstruction of Tai identity in Daikong - Santasombat, Yos (ANU Press, 2008)
The Thai-Yunnan Project is proud to present this English-language version of Professor Yos Santasombat's fascinating ethnography of the Tai in Daikong, southwestern China. It represents a significant contribution to the ethnographic record of the Tai peoples. The village of Lak Chang is located close to the edge of the Tai world and is increasingly embraced by Chinese influence. Professor Yos skilfully weaves ethnographic and historical writing to chart the course of Lak Chang's incorporation into the modern Chinese state. This has been a painful history but what emerges in this account is a sense of Tai cultural identity that is vigorous and adaptive. "The Tai ethnic category is thus a complex and dynamic construct which takes place within the context of changing power relations and socio-economic conditions where the past is reconstructed to give meaning to the present and hope for the future." In his account of the labours, rituals and beliefs of the Tai villagers of Daikong, Professor Yos brings contemporary ethnic identity to their life. Among the patchwork paddyfields and haphazard laneways of Lak Chang we come to a greater understanding of how global and regional processes of modernisation are managed and selectively incorporated by one local community.